2017
DOI: 10.1016/j.jad.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and related stressful life events among Chinese adolescents living in rural areas: A cross-sectional study

Abstract: Aggression was prevalent among Chinese adolescents living in rural areas, and interpersonal problems, health adaption difficulties, and other troubles were considered potential independent risk factors for aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…The prevalence rates of anxiety disorders (e.g., Guo et al, 2016), schizophrenia (e.g., Chan et al, 2015), poor mental health status among older population (Wang et al, 2016), and older adults loneliness (e.g., Zhong et al, 2018) were particularly high in modern China. In rural China, prevalence of reproductive depression (Cao et al, 2015), elderly suicide rate (e.g., Zhong et al, 2016), adolescents aggression (Huang et al, 2017), mental health problems among left-behind children (Tang et al, 2018; Wang J. et al, 2019) and spouses (Nikoloski et al, 2019), students anxiety (e.g., Liu H. et al, 2018), self-stigma (Ran et al, 2018), general depression (Qiu et al, 2018), and hopelessness among lower-class rural residents (Zhang et al, 2019) were high. Mental disorders were significantly associated with increased risk of suicide attempt in rural China (e.g., Sun et al, 2015; Liu et al, 2017; Liu B.P.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rates of anxiety disorders (e.g., Guo et al, 2016), schizophrenia (e.g., Chan et al, 2015), poor mental health status among older population (Wang et al, 2016), and older adults loneliness (e.g., Zhong et al, 2018) were particularly high in modern China. In rural China, prevalence of reproductive depression (Cao et al, 2015), elderly suicide rate (e.g., Zhong et al, 2016), adolescents aggression (Huang et al, 2017), mental health problems among left-behind children (Tang et al, 2018; Wang J. et al, 2019) and spouses (Nikoloski et al, 2019), students anxiety (e.g., Liu H. et al, 2018), self-stigma (Ran et al, 2018), general depression (Qiu et al, 2018), and hopelessness among lower-class rural residents (Zhang et al, 2019) were high. Mental disorders were significantly associated with increased risk of suicide attempt in rural China (e.g., Sun et al, 2015; Liu et al, 2017; Liu B.P.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Raine et al [12] observed that school children with schizotypal traits were likely to suffer from peer victimization. There is also an association between adverse life events and aggression [29] Huang et al found that stressful life events increased the odds of aggression [30]. Considering the above studies, our third hypothesis is that adverse life events may be as important as childhood trauma in mediating the association between schizoid and aggression.…”
mentioning
confidence: 81%
“…Además, en estos trabajos cabe destacar que obtienen este valor ajustado por diferentes variables a controlar a partir de modelos de regresión logística jerárquica. Por otra parte, cabe comentar que la información recogida en este tipo de estudios puede ser analizada con cualquier técnica tradicional de análisis de datos y, por tanto, en algunos estudios se puede observar que se proporciona el estadístico chi-cuadrado como medida de asociación o se aplican técnicas multivariantes de análisis de datos como pueden ser modelos de regresión, y en concreto la regresión logística, o análisis de la varianza, ya que en este caso, además de tener en cuenta el factor de exposición, también se puede tener en cuenta el efecto de las variables a controlar (Huang et al, 2017).…”
Section: Estudios Transversalesunclassified